TWAS Atlas: a curated knowledgebase of transcriptome-wide association studies. Issue Volume 51:Issue D1(2023) (16th October 2022) - Lu, Mingming; Zhang, Yadong; Yang, Fengchun; Mai, Jialin; Gao, Qianwen; Xu, Xiaowei; Kang, Hongyu; Hou, Li; Shang, Yunfei; Qain, Qiheng; Liu, Jie; Jiang, Meiye; et al.
Abstract: Transcriptome-wide association studies (TWASs), as a practical and prevalent approach for detecting the associations between genetically regulated genes and traits, are now leading to a better understanding of the complex mechanisms of genetic variants in regulating various diseases and traits. Despite the ever-increasing TWAS outputs, there is still a lack of databases curating massive public TWAS information and knowledge. To fill this gap, here we present TWAS Atlas (https://ngdc.cncb.ac.cn/twas/ ), an integrated knowledgebase of TWAS findings manually curated from extensive literature. In the current implementation, TWAS Atlas collects 401, 266 high-quality human gene–trait associations from 200 publications, covering 22, 247 genes and 257 traits across 135 tissue types. In particular, an interactive knowledge graph of the collected gene–trait associations is constructed together with single nucleotide polymorphism (SNP)–gene associations to build up comprehensive regulatory networks at multi-omics levels. In addition, TWAS Atlas, as a user-friendly web interface, efficiently enables users to browse, search and download all association information, relevant research metadata and annotation information of interest. Taken together, TWAS Atlas is of great value for promoting the utility and availability of TWAS results in explaining the complex genetic basis as well as providing new insights for human health and disease research.